New species of Agathodesmus Silvestri, 1910 from Australia (Diplopoda, Polydesmida, Haplodesmidae) - Mesibov, Robert (Pensoft Publishers, 2013)
Abstract. The genus Agathodesmus Silvestri, 1910 is speciose and widespread in high-rainfall parts of eastern Australia. In addition to the type species Agathodesmus steeli Silvestri, 1910 and Agathodesmus johnsi Mesibov, 2009 from New South Wales and Agathodesmus bucculentus (Jeekel, 1986) from Queensland, the following 18 new species are recognised: Agathodesmus adelphus sp. n., Agathodesmus aenigmaticus sp. n., Agathodesmus agnus sp. n., Agathodesmus anici sp. n., Agathodesmus gayundah sp. n., Agathodesmus hahnensis sp. n., Agathodesmus kerensis sp. n., Agathodesmus kirrama sp. n., Agathodesmus millaa sp. n., Agathodesmus parapholeus sp. n., Agathodesmus quintanus sp. n., Agathodesmus sagma sp. n., Agathodesmus summus sp. n. and Agathodesmus yuccabinensis sp. n. from Queensland; Agathodesmus carorum sp. n. from New South Wales and Victoria; Agathodesmus bonang sp. n. and Agathodesmus morwellensis sp. n. from Victoria; and Agathodesmus chandleri sp. n. from South Australia.